THE LENTERA ANAK FOUNDATION'S COMMUNICATION STRATEGY ABOUT THE HAZARDS OF CIGARETTES THROUGH THE #SATUPUNTUNGSEJUTAMASALAH CAMPAIGN - Haryono, Cosmas Gatot; Prasetyo, Eko Adit; Reyes, Rowena Capulong (ASPIKOM Jabodetabek Region, 2022)
The purpose of this study is to define and describe the Lentera Anak Foundation's (YLA) usage of communication methods. YLA is a social organization that works to fulfill children's rights in Indonesia and regulate issues that affect children. Researchers chose YLA because they are interested in public communication efforts such as the #SatuPuntungSejutaMasalah (ASingleCount) action, which aimed to raise awareness about the harmful effects of smoking. The researchers sought to know not only what techniques the organization utilized in the campaign and present the difficulties and opportunities they encountered but also to make meaning of the contribution it offered to society. This study employs a constructivist framework and a case study method. The findings, gathered through structured interviews and observation, demonstrated YLA's communication strategy delivering ten previously determined themes about the impact of cigarette butts. #SatuPuntungSejutaMasalah campaign utilized what the researchers termed as CORE Communication tactics: Collaboration for planning, scenario analysis, management, and issues; Organization for development of objectives, content, media, and strategies; Relevance for execution or implementation and the final stage, Engagement for assessment of the outcomes of the efforts performed